Freedom is a feast : a novel - Puyana, Alejandro (Little, Brown and Company, 2024)
"In the tradition of Isabel Allende's career-launching debut, The House of the Spirits, a multigenerational, Latin American saga of love and revolution in which a young man abandons his family for the cause--and receives a late-life chance at redemption." -- Publisher annotation.